Visual surveying control of an autonomous underwater vehicle - Magsino, Elmer R. (Animo Repository, 2014)
This paper implements a visual surveying control in providing motion control to an autonomous underwater vehicle (AUV). The AUV, which has a dimension of 35.5 cm by 16.5 cm, has five motors that are used to provide the necessary motions. Three motors are used for vertical movements while the remaining two are used for the AUV's horizontal movements. A programmable embedded vision sensor mounted inside the AUV processes and analyzes acquired information from its camera and then generates specific commands to be executed by the AUV. Visual surveying for motion control is achieved by recognizing color and tracking objects of a predefined shape. Color recognition aids the AUV to identify a specific color while object tracking makes the submarine to automatically move towards an object in response to its recognized color. © 2014 IEEE.